Determinación del requerimiento hídrico de los cultivos de maíz (Zea maíz L.), pimiento (Capsicum annuum L.) y soya (Glycine max L.) en la zona de Babahoyo provincia de Los Ríos - Montero Zúñiga, Wilmer Edinson (2022)
Corn consumes about 500 mm to 700 mm of rainfall well distributed throughout the growing season; but, even that amount of rainfall is not enough if moisture cannot be stored within the soil, due to shallow soil intensity or runoff, or if evaporation demand is simply too noticeable due to high temperatures and relative humidity. Water requirements for a potential production of bell pepper plants are between 600 and 1 250 mm depending on the year. Peppers are sensitive to water stress, both due to excess and insufficient humidity. Water consumption is 454 mm with a maximum of 7.6 mm day-1. The time between biomass production and water consumption is between 1.2 and 1.6 kg m3, and higher water productivity has also been located in some components of the world. Depending on climate, soil, cultivar, and crop control practices, soybean evapotranspiration can range from 300 mm to 800 mm. The accumulated ET depends on the number of days between emergence and physiological adulthood (R7 stage) and the last date depends on the adult institution (GM) chosen. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose of informing the reader about the importance of the water requirement of corn, bell pepper and soybean crops in the area of Babahoyo, province of Los Ríos. From the above, it was determined that the water requirement of the crop represents the volume of water needed to compensate the evapotranspiration loss of the crop. For proper irrigation control and economic water savings, a correct estimation of crop water requirements is essential. The reference evapotranspiration (ETO) and the crop coefficient (KC) emerge as one of the key elements to estimate crop water requirements.